2021
DOI: 10.3390/app11114770
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D-Imaging of Semiconductor Chips Using THz Time-of-Flight Technique

Abstract: In this study, we developed a rapid three-dimensional (3D) time-of-flight imaging tool for inspection of packaged semiconductor chips, using terahertz (THz) time-domain spectroscopy techniques. A high-speed THz system based on the optical sampling by cavity tuning technique is incorporated with a 2-axis galvano scanner to deliver a scanning speed of more than 100 Hz/pixel with a signal-to-noise ratio larger than 20 dB. Through the use of the Hilbert transformation, we reconstruct the 3D structure of the packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…We used a delay-scan range of Δ T = 100 ps, which corresponds to a vertical range of 15 mm in the case of free-space propagation. Here, the time delay can be converted into depth information, in which 1 ps corresponds to 0.15/ n mm in the reflection geometry, where n is the refractive index of the materials [ 33 , 34 ]. The images were recorded as a single binary file, which can be reconstructed using home-built analyzing software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a delay-scan range of Δ T = 100 ps, which corresponds to a vertical range of 15 mm in the case of free-space propagation. Here, the time delay can be converted into depth information, in which 1 ps corresponds to 0.15/ n mm in the reflection geometry, where n is the refractive index of the materials [ 33 , 34 ]. The images were recorded as a single binary file, which can be reconstructed using home-built analyzing software.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, rapid THz-TOF imaging methods have been introduced for the inspection of packaged integrated circuits and defects in insulating materials [ 33 , 34 ]. An imaging rate of 100–200 Hz/pixels has been achieved based on the THz–TDS technique where fast time-delay scanning methods have been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of epoxy molding compounds (EMCs) in the package generally might affect the performance of encapsulated detectors, and this influence needs to be evaluated. Multiple studies of various EMCs in the THz range [ 29 , 30 , 31 ] indicated their very similar refractive index values of , n = 1.897–1.940, and , respectively. The obtained small variations of the refractive index were attributed to differences in the silica filler content [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Only one high-end laser is typically used for this technique, but it is of course limited by physically moving parts. To date, scan rates of a few hundred Hz have been demonstrated 9 , 10 . PHIRE (parallel heterodyne interferometry via rep-rate exchange), a conceptually similar single-laser technique, was demonstrated for use in dual-comb interferometry 11 , where kHz scan rates were achieved (164 kHz in the case of raw acquisitions, slowed to a few kHz when averaging was used to improve the signal quality).…”
Section: Introductionmentioning
confidence: 99%